Blissfully unmarried - Shaw, Derrick; Ames, Teddy; Ruby Street Productions; Leomark Studios (Firm) ([Delaware] : Ruby Street Productions, 2013)
John Haw is a recently divorced man who is having a rough time adapting to single life. He hates his environment and his job; but most of all he hates his ex-wife. While having a terrible day at work, John is robbed then suspended all in the same day. Just before the straw can break the camel's back, John meets an incredible Asian woman that turns out to be the spark he needs to turn his luck around. In a split second, his entire life is changed when he scratches off a lottery ticket worth one million dollars. Once his ex-wife finds out about his newfound wealth, she springs into a plan of action, attempting to acquire as much of his fortune as she possibly can.
Originally released as a motion picture in 2013.
Teddy Ames, Kinda Stroud, Asaki Kuruma.
Cinematographer, Jeremy Ginsberg ; editor, Thomas Tang ; music, Jeremy Benson, Jonathan Floyd, Randy America.
Contains strong language. Viewer discretion is advised.
In English; additional English subtitles.
Best feature, 2013, Back in the Box Film Competition
Keywords: Divorced men -- Drama; Man-woman relationships -- Drama; Feature films; Comedy films; Internet videos; Streaming video